Classroom Collective Bargaining Simulation : How Close to the Real Thing - Tracy, L.; Peterson, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
The use of games and simulations as means of instruction is particularly appropriate to a behavioral process such as collective bargaining. The author describes, analyses and evaluates one which is used at the University of Washington